Assessment of Microleakage of a Composite Resin Restoration in Primary Teeth Following Class III Cavity Preparation Using Er, Cr: YSGG laser: An In Vitro Study - Subramaniam, Priya; Pandey, Annu (Journal of Lasers in Medical Sciences, 2016)
Introduction: Marginal seal integrity is important for a successful adhesive dental restoration. Alterations caused by laser irradiation in the enamel and dentin surface can affect the marginal integrity of adhesive restorations. The aim of this study was to evaluate the microleakage of a composite resin restoration in primary teeth following laser irradiation of enamel and dentin. Methods: Forty freshly extracted sound human primary maxillary and mandibular anterior teeth were used in this study. The teeth were randomly divided into two groups (I and II), with 20 teeth in each. In group I, proximal cavities (Class III) were prepared using an airotor hand –piece and diamond bur. The cavities were etched for 15 seconds with 35% phosphoric acid gel, rinsed with water for 15 seconds, air dried and a bonding agent was applied onto the cavity surfaces and light cured for 20 seconds. The cavities were restored with composite resin and light cured for 40 seconds. In group II, proximal (Class III) cavities were prepared using Erbium, Chromium: Yttrium Scandium Gallium Garnet (Er,Cr:YSGG) (Er,Cr:YSGG) (Biolaseiplus, wave length 2.78 μm). The cavity was then rinsed, air dried and without etching, a bonding agent was applied and light cured for 20 seconds. The cavities were restored in the same manner as that of group I. The treated teeth were mounted on acrylic resin blocks and were subjected to a thermocycling regimen. Following, the teeth were immersed in 2% methylene blue for 24 hours. The teeth were sectioned longitudinally in a bucco-lingual direction using a diamond disc at slow speed. The sections of all the groups were examined under a stereomicroscope for micro-leakage. Results: The mean scores for microleakage in group I was 1.95 ± 1.31 and in group II it was 1.4 ± 1.27. There was no significant difference between the two groups (P = 0.882). Conclusion: No significant difference in microleakage was noticed between the composite resin bonded to lased enamel and dentin and the teeth preparedwith conventional method.